2015
DOI: 10.1002/ajmg.a.37240
|View full text |Cite
|
Sign up to set email alerts
|

Congenital limb deficiencies in Alberta—a review of 33 years (1980–2012) from the Alberta Congenital Anomalies Surveillance System (ACASS)

Abstract: The birth prevalence of limb deficiencies in Alberta has been fluctuating. The objectives were to examine patterns and temporal trends of congenital limb deficiencies in Alberta and compare rates with those of other jurisdictions. The Alberta Congenital Anomalies Surveillance System data on live births, stillbirths, and terminations of pregnancy (<20 weeks gestation) occurring between 1980 through 2012 with the ICD-10 Royal College of Paediatrics and Child Health Adaptations codes Q71-Q73 (limb reduction defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
58
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 48 publications
12
58
3
Order By: Relevance
“…The incidence of a split hand/foot is even more rare (0.5/10 000; 0.05%). 15,16 The high incidence of limb reduction defects among embryonic miscarriages with full trisomy 15 detected by embryoscopy in the present study, and another case of a split hand in a minimal expression recorded in a liveborn with mosaic trisomy 15, 17 indicate that limb reduction defects and craniofacial abnormalities are a common feature of trisomy 15. The strong association of transverse limb reduction defects with trisomy 15 has not been reported previously in the published literature.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The incidence of a split hand/foot is even more rare (0.5/10 000; 0.05%). 15,16 The high incidence of limb reduction defects among embryonic miscarriages with full trisomy 15 detected by embryoscopy in the present study, and another case of a split hand in a minimal expression recorded in a liveborn with mosaic trisomy 15, 17 indicate that limb reduction defects and craniofacial abnormalities are a common feature of trisomy 15. The strong association of transverse limb reduction defects with trisomy 15 has not been reported previously in the published literature.…”
Section: Discussionsupporting
confidence: 49%
“…The incidence of limb reduction defects in our cohort is 22% (10 embryos with a terminal transverse limb reduction defect, 3 with a split hand), which is much higher than that reported in live births (5.6/10 000; 0.6%). The incidence of a split hand/foot is even more rare (0.5/10 000; 0.05%) …”
Section: Discussionmentioning
confidence: 99%
“…Transverse terminal and longitudinal preaxial are the most common anatomic subtypes reported in the literature, but there is variation in the relative distribution of each subtype. For transverse terminal defects, Riaño et al () reported 49.3% and Castilla et al () 43.3%; whereas Lin et al (), Froster‐Iskenius and Baird (), Gold et al () and Bedard et al () reported 35.1, 34.2, 28.9, and 18.9%, respectively. In populations in which transverse terminal defects are less common, there is an increase in longitudinal defects, particularly preaxial.…”
Section: Discussionmentioning
confidence: 97%
“…In populations in which transverse terminal defects are less common, there is an increase in longitudinal defects, particularly preaxial. For longitudinal defects, Riaño et al () reported 27.4% (9.6% postaxial and SH/SF complex), Castilla et al () 23.1% (13.1% preaxial), Froster‐Iskenius and Baird () 46.8% (27.6% preaxial), Lin et al () 51.3% (26.2% split hand/split foot), Gold et al () 54.1% (24.7% preaxial), and Bedard et al () 66.0% (22.4% preaxial and postaxial combined).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation